Criminal Tax Law in the U.S. – A Model for Improving German Criminal Tax Law Enforcement? - Matthias Zahner
Steuerkriminalität, Steuerrecht, Strafrecht, Strafe, Vereinigte Staaten, Deutschland, Tax fraud, Tax law, Criminal law, Penalty, United States, Germany